2013
DOI: 10.1186/2193-1801-2-652
|View full text |Cite
|
Sign up to set email alerts
|

Can levels of antioxidants in synovial fluid predict the severity of primary knee osteoarthritis: a preliminary study

Abstract: BackgroundLittle is known about differences in amounts of antioxidants or oxidative stress at different stages of knee osteoarthritis. This study investigated the relationship between concentrations of antioxidants, iron and lipid peroxidation in synovial fluid and levels of severity of primary knee osteoarthritis.Materials and methodsFrom 2011 to 2013, 23 patients (mean age, 66.7 ± 7.6 years) with primary knee osteoarthritis were recruited. Patients were divided into 2 groups based on pre-treatment knee socie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Specifically, Sutipornpalangkul et al [ 53 ] found that the vitamin E concentration in synovial fluid was inversely related to primary knee OA severity in 32 patients, indicating that oxidative stress increased as the clinical severity of OA increased. A similar study later confirmed this result [ 54 ]. Regarding the therapeutic effect of vitamin E supplementation, Bhattacharya et al [ 55 ] conducted a cohort study in which the levels of antioxidant enzymes, such as GPX and MDA in plasma, were estimated in 40 healthy individuals (control group) and in 40 OA patients 50–70 years old before and after 3 months of vitamin E supplementation; the patients were divided into group I (no supplementation) and group II (200 mg/day vitamin E supplementation.…”
Section: Potential Association Between Ferroptosis and Oa: Clinical F...supporting
confidence: 74%
“…Specifically, Sutipornpalangkul et al [ 53 ] found that the vitamin E concentration in synovial fluid was inversely related to primary knee OA severity in 32 patients, indicating that oxidative stress increased as the clinical severity of OA increased. A similar study later confirmed this result [ 54 ]. Regarding the therapeutic effect of vitamin E supplementation, Bhattacharya et al [ 55 ] conducted a cohort study in which the levels of antioxidant enzymes, such as GPX and MDA in plasma, were estimated in 40 healthy individuals (control group) and in 40 OA patients 50–70 years old before and after 3 months of vitamin E supplementation; the patients were divided into group I (no supplementation) and group II (200 mg/day vitamin E supplementation.…”
Section: Potential Association Between Ferroptosis and Oa: Clinical F...supporting
confidence: 74%
“…Glutathione (GSH) is a naturally occurring tripeptide with nucleophilic and reducing properties that play a central role in the antioxidant system of most aerobic cells. Since GSH is a naturally occurring antioxidant with several functions including detoxification of xenobiotics and removal of hydroperoxides and free radicals, GSH concentration has been determined in many studies on oxidative stress 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…GSH is an important antioxidant, which is essential in the regulation of protein disulfide bonds and the treatment of electrophiles and oxidants. The determination of the GSH concentration is indispensable in many studies on oxidative stress [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%